DEVELOPMENT OF SCIENTIFIC AND METHODICAL APPROACHES TO ESTIMATE THE QUALITY OF THE INFORMATION RESOURCE OF A TRANSPORT AND LOGISTIC COMPANY - T. Bogdanova; K. Kuznetsov (Вестник университета)
The article shows the use of the process approach for the development of scientific and methodological approaches to assessing the quality of the transport and logistics company’s information resource. The problems of formalization of the quality assessment of the information resource are considered. A method of formalization based on the decomposition of composite characteristics into simple elements is proposed. The information support for the business process and the composite characteristics of the reliability, usefulness and timeliness of the information resource, is considered, and the simple elements compiling them are identified. The use of the developed methodology for identifying problem areas in the information support of a transport and logistics company are considered. Scientific and methodological approaches to the assessment of the quality of information support for the company's market environment are considered. An example of a study of the effectiveness of information support for a transport and logistics company is given.